1994
DOI: 10.1086/173912
|View full text |Cite
|
Sign up to set email alerts
|

Detection of signature consistent with cosmological time dilation in gamma-ray bursts

Abstract: If gamma-ray bursters are at cosmological distances-as suggested by their isotropic distribution on the sky and by their number-intensity relation-then the burst proles will be stretched in time, by an amount proportional to the redshift, 1 + z. We h a v e tested data from the Compton Gamma Ray Observatory's Burst and Transient Source Experiment (BATSE) for such time dilation. Out of 590 bursts observed by B A TSE, 131 bursts were analyzed; bursts with durations shorter than 1.5 s were excluded. We used three … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
125
1

Year Published

1995
1995
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(133 citation statements)
references
References 7 publications
7
125
1
Order By: Relevance
“…This also implies that the cosmological time dilatation should not affect significantly the observed distribution of T 90 , which therefore is not expected to differ statistically from that of t 90 . We note that several other authors (Wijers & Paczyński 1994;Norris et al 1994;Norris et al 1995) have already suggested that the distribution of T 90 reflects predominantly the distribution of t 90 . Nevertheless, our argumentation based on the mathematical Cramér theorem is new.…”
Section: Analysis Of the Duration Distributionsupporting
confidence: 50%
See 1 more Smart Citation
“…This also implies that the cosmological time dilatation should not affect significantly the observed distribution of T 90 , which therefore is not expected to differ statistically from that of t 90 . We note that several other authors (Wijers & Paczyński 1994;Norris et al 1994;Norris et al 1995) have already suggested that the distribution of T 90 reflects predominantly the distribution of t 90 . Nevertheless, our argumentation based on the mathematical Cramér theorem is new.…”
Section: Analysis Of the Duration Distributionsupporting
confidence: 50%
“…As shown in Bagoly et al (1998), the stochastic variable corresponding to the duration is independent from that of the peak flux. This means that a fixed level of detection, given by the peak fluxes, does not have significant influence on the shape of the detected distribution of the durations (Efron & Petrosian 1992;Wijers & Paczyński 1994;Norris et al 1994Norris et al , 1995. In the case of the fluences, however, a detection threshold in the peak fluxes induces a bias on the true distribution, since fluences and durations are stochastically not independent.…”
Section: Analysis Of the Fluence Distributionmentioning
confidence: 99%
“…However, the interpretation of the duration differences between bright and dim bursts previously attributed to cosmological time dilation (Norris et al 1994) has now become very unclear.…”
Section: A Hubble Relationship For Grbs?mentioning
confidence: 99%
“…The development of new nonlinear time-series analysis tools during the last decade has changed this situation. In particular, it has been found that these tools have rich applications in a broad range of astrophysical situations, which include time analysis of gamma-ray bursts [18], of gravitationally lensed quasars [19] or Xrays within galaxy clusters [20], and of variable white dwarfs [21]. These tools have also been used to analyze theoretical models of stellar pulsations.…”
Section: Introductionmentioning
confidence: 99%